Spatial and directional tuning of serial dependence for tracking eye movements - Goettker, Alexander; Stewart, Emma E. M.; Justus Liebig University Giessen (My University, 2024)
An attractive influence of past sensory experience on current behavior has been observed in many domains ranging from perceptual decisions to motor responses. However, it is unclear what sort of information is integrated across trials, especially for oculomotor behavior. Here we provide a detailed investigation of the spatial and directional tuning of serial dependence for oculomotor tracking. Across multiple experiments, we measured oculomotor responses to sequences of movements: the first movement (prior) could move at different velocities (5 deg/s or 15 deg/s), and could vary in its spatial location or direction relative to the following movement. The second movement (probe) was constant across all experiments and moved at 10 deg/s. We observed that eye velocity for the probe was faster when following the fast prior compared to following the slow prior, replicating attractive serial dependence. Importantly, this effect stayed consistent for distances of up to 30 deg between prior and probe, indicating a retinotopic reference frame. When we manipulated the direction of the prior, we observed that the influence of the prior on eye velocity, as well as eye direction, was stronger for prior directions more similar to the probe direction, and the magnitude of the effect on eye velocity and eye direction was correlated. Across all experiments, we observed that even when the prior moved in the opposite direction, there was a residual attractive effect. This suggests that serial dependence for oculomotor tracking consists of two components, one retinotopic, direction-tuned component and one more general component that is not direction specific.
Keywords: ddc:150